Classification of the Trade Intermediaries and the Variants of their Using in Supply Chains - Alexey Petrovich Tyapukhin (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article includes the classification of the trade intermediaries, typical structures of the recourses supply systems, business-processes and functions, which trade intermediaries executive and also the variants of the channels and chains of the recourses supply systems